Closed Frequent Itemsets Mining Based on It-Tree - Fakir, Youssef; Ahle Touate, Chaima; Elayachi, Rachid; Fakir, Mohamed (Journal of Medical Informatics and Decision Making, 2020)
In the last decade, the amount of collected data, in various computer science applications, has grown considerably. These large volumes of data need to be analysed in order to extract useful hidden knowledge. This work focuses on association rule extraction. This technique is one of the most popular in data mining. Nevertheless, the number of extracted association rules is often very high, and many of them are redundant. In this paper, we propose an algorithm, for mining closed itemsets, with the construction of an it-tree. This algorithm is compared with the DCI (direct counting & intersect) algorithm based on min support and computing time. CHARM is not memery-efficient. It needs to store all closed itemsets in the memory. The lower min-sup is, the more frequent closed itemsets there are so that the amounts of memory used by CHARM are increasing.
Keywords: Data mining; Association rules; frequent closed itemset; CHARM; DCI